Metal (boro-) hydrides for high energy density storage and relevant emerging technologies. (27th November 2020) - Bannenberg, L.J.; Heere, M.; Benzidi, H.; Montero, J.; Dematteis, E.M.; Suwarno, S.; Jaroń, T.; Winny, M.; Orłowski, P.A.; Wegner, W.; Starobrat, A.; Fijałkowski, K.J.; et al.
Abstract: The current energy transition imposes a rapid implementation of energy storage systems with high energy density and eminent regeneration and cycling efficiency. Metal hydrides are potential candidates for generalized energy storage, when coupled with fuel cell units and/or batteries. An overview of ongoing research is reported and discussed in this review work on the light of application as hydrogen and heat storage matrices, as well as thin films for hydrogen optical sensors. These include a selection of single-metal hydrides, Ti–V(Fe) based intermetallics, multi-principal element alloys (high-entropy alloys), and a series of novel synthetically accessible metal borohydrides. Metal hydride materials can be as well of important usefulness for MH-based electrodes with high capacity (e.g. MgH2 2000 mA h g −1 ) and solid-state electrolytes displaying high ionic conductivity suitable, respectively, for Li-ion and Li/Mg battery technologies. To boost further research and development directions some characterization techniques dedicated to the study of M-H interactions, their equilibrium reactions, and additional quantification of hydrogen concentration in thin film and bulk hydrides are briefly discussed. Graphical abstract: Image 1 Highlights: High hydrogen storage capacity can be reached in metal (boro)hydrides. Selected intermetallics may lead to an efficient stationary energy storage. Novel metal borohydrides with varied properties are synthetically made available. Optical sensors based on MH are paving the way for accurate hydrogen sensing. High energy density all-solid-state MH-batteries are predicted compared to oxides.